The effect of eplerenone on the renin‐angiotensin‐aldosterone system of rats with thyroid dysfunction - Dizaye, Kawa (J Pharm Pharmacol, 2019)
OBJECTIVES: This study was conducted to evaluate the effect of eplerenone on the RAAS and kidney function in rats with thyroid hormone disorders. METHODS: This study involved 30 male Wistar albino rats, divided into three groups. The first group (N = 6) served as a control. The second group involved 12 rats with experimentally induced hypothyroidism through receiving propylthiouracil (0.05% w/v) in drinking water for one month, which was divided into two subgroups of six rats each. The first subgroup served as a positive hypothyroid control, and the second subgroup received oral daily dose of eplerenone (100 mg/kg) for 14 days. The third group included 12 rats with induced hyperthyroidism with L‐thyroxin (0.0012% w/v) in drinking water, and rats in this group were also divided into two subgroups. The first subgroup served as a positive hyperthyroid control, and the second subgroup received oral eplerenone 100 mg/kg. RESULTS: Eplerenone indicated a significant increase in renin and angiotensin I from 184.09 pg/ml and 178.66 pg/ml to 603.31 pg/ml and 250.88 pg/ml, respectively, meanwhile, aldosterone indicated no significant changes after inducing hypothyroidism and eplerenone administration. The induction of hyperthyroidism led to a significant increase in angiotensin I from 248.84 pg/ml to 292.22 pg/ml. Oral administration of eplerenone for 14 days caused a significant increase aldosterone from 364.23 pg/ml to 497.02 pg/ml. CONCLUSION: Eplerenone significantly increased the serum renin and angiotensin I in hypothyroid and aldosterone and angiotensin I in hyperthyroid rats. Aldosterone in hypothyroid rats was not changed by eplerenone.